Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1111/j.1365-2923.1990.tb02512.x
|View full text |Cite
|
Sign up to set email alerts
|

The application of basic science concepts to clinical problem-solving

Abstract: This study looks at the relationship between anatomical concepts held by medical students and their clinical application, and develops a testable model of how students use basic science concepts for clinical problem-solving. According to the model, the essential prerequisites to solve a clinical problem using basic science information include the appropriate basic science knowledge, the ability to collect and interpret clinical information, with the key concept being the link that must then be made between cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 4 publications
3
21
0
1
Order By: Relevance
“…Previous research by Cholowski and Chan (1992) found a strong relationship between student nurses’ performance on a clinical problem‐solving task and the quality of their diagnostic reasoning. Similar findings have been obtained from studies with medical students (Balla et al. 1990).…”
Section: Cognitive Factors In Clinical Problem Solvingsupporting
confidence: 88%
“…Previous research by Cholowski and Chan (1992) found a strong relationship between student nurses’ performance on a clinical problem‐solving task and the quality of their diagnostic reasoning. Similar findings have been obtained from studies with medical students (Balla et al. 1990).…”
Section: Cognitive Factors In Clinical Problem Solvingsupporting
confidence: 88%
“…For example, although completion of the freshman writing prerequisite improved student performance in a business communication class, no positive association was observed for the computer literacy prerequisite (Marcal and Roberts, 2000). Similarly, Balla et al (1990) found that basic anatomy knowledge did not positively correlate with the ability of medical students to perform effective clinical diagnoses. Furthermore, nursing students' grades in a research course did not strongly correlate with their grades in the prerequisite statistics course (Grace and D'Aoust, 2006).…”
Section: Introductionmentioning
confidence: 82%
“…The capacity to apply basic sciences knowledge in appropriate clinical situations is a major objective of teaching the basic sciences. However, recent studies indicate that a large number of students are unable to effectively use basic sciences theory in diagnostic problem-solving (Whelan 1988;Ramsden, Whelan and Cooper 1989;Balla, Biggs, Gibson and Chang 1990;Patel, Evans and Kaufman 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the organization and development of concepts would appear to be the key to good clinical reasoning and diagnosis (Balla, Biggs, Gibson and Chang 1990), in which the goal is to explain the underlying causal mechanism(s) of the clinical signs and symptoms, as a prerequisite step to making effective treatment and clinical management decisions.…”
Section: Introductionmentioning
confidence: 99%